Elizabeth Bowen's psychoanalytic fiction - Coulson, Victoria (Midcentury modern writers., 2020)
This book provides a new account of Bowen's fiction that highlights in particular the force and originality of Bowen's virtually psychoanalytic thinking about development, sexuality and gender.